2015
DOI: 10.18632/oncotarget.4056
|View full text |Cite
|
Sign up to set email alerts
|

Mutated Fanconi anemia pathway in non-Fanconi anemia cancers

Abstract: An extremely high cancer incidence and the hypersensitivity to DNA crosslinking agents associated with Fanconi Anemia (FA) have marked it to be a unique genetic model system to study human cancer etiology and treatment, which has emerged an intense area of investigation in cancer research. However, there is limited information about the relationship between the mutated FA pathway and the cancer development or/and treatment in patients without FA. Here we analyzed the mutation rates of the seventeen FA genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…32 Our previous studies reported that, at both the functional and genetic level, impairment to the FA pathway contributes to the development of BC. 10,11 The studies presented herein demonstrate for the first time that the FAVL induced impairment of the FA pathway contributes to BC at the metabolic level. In this study, we systematically profiled metabolites in FAVL-low and -high cells using GC-TOFMS and UPLC-MS/MS.…”
Section: Discussionmentioning
confidence: 69%
“…32 Our previous studies reported that, at both the functional and genetic level, impairment to the FA pathway contributes to the development of BC. 10,11 The studies presented herein demonstrate for the first time that the FAVL induced impairment of the FA pathway contributes to BC at the metabolic level. In this study, we systematically profiled metabolites in FAVL-low and -high cells using GC-TOFMS and UPLC-MS/MS.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, somatic mutations occurring in at least 22 FA genes are also important for the development of human cancer. The human genome project provided a useful resource in finding a considerable rate of impairment to the FA signaling pathway (then known of only 17 FA genes) with a mean rate of about 30% in non-FA human cancers [20]. Most importantly, this rate is statistically and positively associated with the tumor stages ( p <0.05).…”
Section: Fa Signaling and Effective Tools For Cancer Prevention mentioning
confidence: 99%
“…A considerable cases of cancers arise along with an abnormal FA pathway [24] , but a certain percentage of cancer cases with a proficient FA pathway, which conceptually provides a tumor-killing barrier to chemo- and radiotherapy, given its capability in DNA damage repair/ maintenance of genome stability. Thus, inhibition of this pathway may sensitize the tumor cells to DNA damage caused by chemo- or radio-therapies.…”
Section: Fa Pathway-targeted Agents In Cancer Therapymentioning
confidence: 99%
“…So far, the crucial roles of FANCD2 playing in the FA pathway are attracting more and more attention. The dysfunction of FANCD2 derived from genetic mutation either hetero- or homozygosity has been detected in a variety of cancers [2023] and concluded to be positively correlated with cancer development [24] . Herein, we review recent studies on the underlying mechanisms of FANCD2 in the suppression of tumor development.…”
Section: Introductionmentioning
confidence: 99%